PENGEMBANGAN SISTEM PENGEREMAN TURBIN ANGIN SUMBU HORIZONTAL MENGGUNAKAN KONTROL PID - Fahriannur, Ahmad; Agustin, Afifah Putri; Rahmanto, Dedi Eko; Nuruddin, Mochammad (P3M Politeknik Negeri Indramayu, 2024)
Horizontal axis wind turbines will generate voltage if the turbine rotates due to wind gusts. The bigger the wind blows, the faster the turbine spins and the greater the voltage generated. The braking system is needed for wind turbine protection when it receives very large wind speeds. This system is built using PID control based on microcontroller with reference to the output voltage. There are 2 units resistor designed as voltage sensors to the wind turbine output voltage. In testing, the wind turbine is rotated using artificial wind which is generated through a blower measuring 1.3 x 1.3 x 0.3 m, with a maximum wind speed is 11 m/s. The sistem uses PID kontrol which is used to brake wind turbine rotation and regulate its output voltage. Determination of constant parameters for proportional constant (Kp), integral constant (Ki), and Derivative constant (Kd) were obtained for Kp = 0.139, Ki = 0.715, and Kd = 0.006 respectively. The output voltage of the wind turbine can reach 60 volts and then controlled up to 24 volts according to the battery voltage requirements. In the test results, the control system managed to regulate the wind turbine voltage at 24 volts with a steady state error of 6.62%